Following the ball: African soccer players, labor strategies and emigration across the Portuguese colonial empire, 1949-1975 - Todd Cleveland (Cadernos de Estudos Africanos)
This article examines the experiences of African soccer players who relocated to Portugal from 1949 to the end of the colonial era in 1975, attempted to negotiate this politically-charged environment and strove to consolidate their post-athletic futures. I argue that despite the otherwise extraordinary nature of these individuals’ lives, their experiences suggest strong continuities with, and affinities to, well-established African labor strategies, including seeking occupational advice from more senior employees (i.e., fellow players) and engaging in secondary migration in order to improve working and living conditions. The article also contends that the process of cultural assimilation that helped players adjust to their new surroundings commenced in the urban, “colonized spaces” of Africa and, thus, well before they arrived in Portugal.